What Counts as Scientific Data? A Relational Framework. Issue 5 (December 2015) - Leonelli, Sabina
Abstract : This paper proposes an account of scientific data that makes sense of recent debates on data-driven and 'big data' research, while also building on the history of data production and use particularly within biology. In this view, 'data' is a relational category applied to research outputs that are taken, at specific moments of inquiry, to provide evidence for knowledge claims of interest to the researchers involved. They do not have truth-value in and of themselves, nor can they be seen as straightforward representations of given phenomena. Rather, they are fungible objects defined by their portability and prospective usefulness as evidence.